Exchange bias effect in hybrid improper ferroelectricity Ca2.94Na0.06Mn2O7 - Li, Songyang; Wang, Shouyu; Lu, Yangong; Zhang, Chuang; Yang, Xiaoxia; Gao, Ju; Li, Dejun; Zhu, Yun; Liu, Weifang (AIP advances, 2018)
The hybrid improper ferroelectricity Ca3Mn2O7 (CMO) has been a subject of remarkable interest due to potential multiferroicity. In this paper we synthesized CMO and Ca2.94Na0.06Mn2O7 (CNMO) ceramics and investigated their structural and magnetic properties. It is found that Na doping effectively weakens the structural distortion as decreasing the orthorhombic distortion and Jahn-Teller distortion. Although both samples undergo an antiferromagnetic transition at temperature around 111 K, the exchange bias and coercive fields increase in CNMO. Such increased exchange bias field could be explained within a model of size-variable nanoscale ferromagnetic clusters embedded in an antiferromagnetic matrix.